A Survey Analysis of Students Spending Pattern of the Selected Colleges in Kolkata, West Bengal - Ghorai, Satyajit (International Journal of Engineering and Management Research, 2025)
This study presents a comprehensive account of expenditure behavior of students of some chosen colleges in Kolkata, West Bengal. Through the descriptive research method, primary level data were gathered using standardized questionnaires from 185 undergraduate students in relation to categories of expenditure, determinants, and demographic factors. The study reveals that huge numbers of students exhibit sensible monthly expenditure, spending below INR 1,000 on essential goods such as food, transport, and social excursions, portraying prudent economic behavior. High proportions of students maintain stable savings tendencies and are influenced by personal decisions and parental encouragement. Demographic factors, particularly income and source of funding, have a strong influence on attitudes towards spending, as revealed through statistical tests such as chi-square tests and measures of association like contingency coefficients. The study further identifies that spending frequency has a strong relationship with spending behavior, with shopping by month having a strong association. Further, the effect of extraneous factors like peer influence and media influence also varies across spending behaviors. The findings emphasize the demand for tailor-made financial literacy interventions to boost careful expenditures and savings amongst learners. Overall, such localized awareness may guide policy-makers, instructors, and monetary entities towards upholding financially accountable acts among scholars within Kolkata.